Pengaruh Fitur Pengaduan di Shopee terhadap Loyalitas Konsumen: Studi pada Pengguna Aktif Shopee di Kota Surakarta - Nur Fitri Kurniasari; Cahya Herdjona Kurniawan; Margaretha Evi Yuliana (Universitas Duta Bangsa Surakarta, 2025)
Shopee is one of the largest e?commerce platforms in Indonesia that continually strives to enhance its service quality, including through the implementation of a complaint feature. This study aims to analyze the effect of the complaint feature on Shopee customer loyalty. A quantitative approach was employed using a survey method and Structural Equation Modeling based on Partial Least Square (SEM?PLS) with the assistance of SmartPLS version 3 software. The sample consisted of 100 active Shopee users who had utilized the complaint feature. The findings indicate that the complaint feature has a positive and significant impact on customer loyalty. The better consumers perceive this feature, the higher their loyalty toward Shopee will be.